PENGARUH SENAM LANSIA TERHADAP PERUBAHAN TEKANAN DARAH PADA LANSIA DI PANTI TRESNA WEDHA ILOMATA KOTA GORONTALO - Muh. Isman Jusuf; Rona Febriyona (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Health problems are most common in the elderly is a degenerative disease, one of which is hypertension, and one factor that causes hypertension in the elderly is the lack of physical activity, physical activity such as exercise done regularly can improve the durability of heart so that it can lower blood pressure the purpose of this study was to determine the effect of elderly exercisers to changes in blood pressure in elderly hypertensive patients in PSTW IlomataGorontalo city.The study design used was quasi experimental one group pre test post test. Variables in this study that the Elderly Gymnastics (independent) and blood pressure changes (dependent). The population was elderly with hypertension were 30 samples in this study using a sample Purposife numbered 27 people. Data were collected using a mercury sphygmomanometer, stethoscope and observation sheet then the results were analyzed by T test Dependent.The survey results revealed that there is significant influence between Gymnastics Elderly with changes in systolic and diastolic blood pressure in elderly hypertensive patients in PSTW Iloamta Gorontalo City. Based on the results of the data analysis it can be concluded that there is a significant effect among elderly exercisers to changes in systolic and diastolic blood pressure in elderly hypertensive patients in PSTW IlomataGorontalo city.